The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jfb13040249
|View full text |Cite
|
Sign up to set email alerts
|

Collagen as a Biomaterial for Skin and Corneal Wound Healing

Abstract: The cornea and the skin are two organs that form the outer barrier of the human body. When either is injured (e.g., from surgery, physical trauma, or chemical burns), wound healing is initiated to restore integrity. Many cells are activated during wound healing. In particular, fibroblasts that are stimulated often transition into repair fibroblasts or myofibroblasts that synthesize extracellular matrix (ECM) components into the wound area. Control of wound ECM deposition is critical, as a disorganized ECM can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 171 publications
0
14
0
1
Order By: Relevance
“…Lastly, during the maturation step, cells are engaged in the secretion of molecules involved in the extracellular matrix remodeling, such as collagen type I, which represents the most abundant protein synthetized and secreted by fibroblasts [ 29 ]. As collagen I secretion increased after SS administration, both in a standard and in an inflamed-environment condition, the authors assumed that a wound healing process could be definitely facilitated by SS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, during the maturation step, cells are engaged in the secretion of molecules involved in the extracellular matrix remodeling, such as collagen type I, which represents the most abundant protein synthetized and secreted by fibroblasts [ 29 ]. As collagen I secretion increased after SS administration, both in a standard and in an inflamed-environment condition, the authors assumed that a wound healing process could be definitely facilitated by SS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter aspect, the in vitro migration assay performed here demonstrated that Dental SKIN BioRegulation (Guna S.p.a., Milan, Italy) coating has induced a significant improvement in wound healing at 24 h and a complete reconstitution of the cell monolayer after 48 h compared to CTRL, allowing a more aligned and regular orientation of hGF in the direction of wound closure. In support of this evidence, there is a large literature on the beneficial effects of collagen in wound healing in different tissue districts, including the oral ones [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 93%
“…Knowledge about collagen has been exponentially increased in the past decades. Whereas scientific community in the 1970s talked about only four types of genetically distinct collagens [ 23 ], at present it is generally accepted that collagen superfamily comprises up to 28 members that differ from each other in molecular composition as well as in their supramolecular organization within the ECM [ 24 , 25 , 26 , 27 ]. The occurrence of an additional collagen type, called collagen XXIX, has been also claimed by some authors [ 28 , 29 ], although, given that COL29A1 gene was shown to be identical to the COL6A5 gene and that the a1(XXIX) chain corresponds to the a5(VI) [ 30 ], collagen XXIX is not generally accepted as a genetically distinct family [ 24 ].…”
Section: Understanding Collagen Worldmentioning
confidence: 99%